Cognitive Flexibility, Procrastination, and Need for Closure Predict Online Self-Directed Learning Among Pakistani Virtual University Students - Itbar Khan (International Islamic University Islamabad, 2021)
This study investigated the relationship between students’ self-directed online learning and their everyday psychological factors often associated with learning in general.Total 140 Virtual University students in Pakistan completed measures of online self-directed learning and psychological factors, including cognitive flexibility, procrastination, and need for closure.  Regression analyses indicated that the less students procrastinate in general, the more students embraced cognitive flexibility, and the less they impulsively sought quick solutions, the more likely they reported effective online self-directed learning.  In contrast, younger students, had a need for quick answers, procrastinate in general, and who embraced cognitive flexibility, were more likely to report ineffective online self-directed learning.The results suggest that students may be given training on how to avoid procrastination. Students need for closure can be eased by quizzes throughout the semester and students may be taught alternatives for encouraging cognitive flexibility.